Fuzzy Logic Controller Design for Smart Watering System of Rose Cultivation - Arifin, Samsul; Mukti, Fransiska Sisilia; Aziz, Aynan Salsabilah (Department of Informatics Engineering, 2023)
The traditional methods of rose cultivation often rely on manual irrigation practices, which may not always be precise or efficient. Additionally, the cost associated with implementing automated irrigation systems has been a limiting factor for many farmers. This research addresses these challenges by exploring the integration of Fuzzy Logic Controller (FLC) technology and low-cost electronic devices to develop an automated irrigation system tailored for rose cultivation, aiming to enhance precision and accessibility in agricultural practices. The study demonstrates the effectiveness of this approach in optimizing watering practices, showcasing a notable level of accuracy in providing irrigation recommendations. Moreover, the implementation of low-cost electronic devices enhances the accessibility and feasibility of such smart irrigation systems. The research lays a foundation for advancements in precision agriculture, particularly in the domain of rose cultivation, with potential implications for broader agricultural practices.